Clean and Healthy Behaviors At Al-Jam’iyatul Wasliyah Orphanage - Anissa Syafira; Chindy Ingraini; Cindy Puspita Ningrum; Meilisa Luthfiah; Muhammad Alawi; Tarisa Nazlita Saragih (Pena Cendekia Insani, 2020)
Clean and Healthy Life Behavior are all health behaviours carried out because of personal awareness so that families and all members can help themselves in the health sector and have an active role in community activities. An orphanage is a place to live or accommodate children who do not have family or parents while they still need the love and education they deserve. Al-Jam'iyatul Wasliyah Orphanage is an orphanage built to accommodate children, such as orphans, orphans, poor children, and abandoned children, to increase the knowledge of the orphanage children, a foundation was built to carry out their education, where this foundation is the same as schools in general, namely Madrasah, Junior High School, and Senior High School. The purpose of this study was to determine the extent to which children are familiar with healthy living and to know the motivating and inhibiting factors for implementing healthy living at the Al-Jam'iyatul Wasliyah orphanage. This study uses a qualitative descriptive method through interviews and questionnaires with children. From the research that has been carried out, it is obtained that from 24 samples, 20 children at the Al-Jam'iyatul Wasliyah Orphanage have implemented clean and healthy living behaviours, and four children in the orphanage are still not implementing healthy living due to the lack of awareness of teenagers themselves about behavioural health. However, this states that the Al Jami'iyatul Washliyah Orphanage children have been living a healthy life well..